ANALISIS PERHITUNGAN HARGA POKOK PRODUKSI MENGGUNAKAN METODE FULL COSTING DALAM PENENTUAN HARGA JUAL PADA PEMUDA MULIA COMPANY DI RANTAU PULUNG - Helpianti, Helpianti (Sekolah Tinggi Ilmu Ekonomi Nusantara Sangatta, 2024)
The purpose of this study was to determine the cost of production of Pemuda Mulia Company in obtaining greater profits. This type of research is quantitative research. Data is collected by viewing or analyzing documents made by Pemuda Mulia Company. This study is to analyze the determination of the selling price at Pemuda Mulia Company by using the full costing method. Based on the calculation of the cost of production using the full costing method, it is higher than the calculation according to the Pemuda Mulia Company. The total cost of production using the full costing method of Balado cassava chips is Rp. 4.776.945 while with the Pemuda Mulia Company method, Rp. 3.948.733. Produce a calculation difference of Rp. 828,212. The factor that causes the difference is due to the calculation that uses the full costing method to calculate all production costs compared to the Pemuda Mulia Company method not to calculate the depreciation cost of assets